Optimisation of creativity students on finite element analysis and simulation learning using industrial product - Setiadi, Bayu Rahmat; Amalia, Ayu Fitri (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2025)
The challenge of industrial product competitiveness often lies in product design, where industries face obstacles in producing prototypes suitable for commercialization. Collaboration between universities and small and medium enterprises offers opportunities to develop diversification and product capacity through learning. This research engages students in solving industrial problems creatively using Finite Element Analysis (FEA) and simulation for product development. Conducted at the Product Design Laboratory, Department of Mechanical Engineering Education, Universitas Negeri Yogyakarta, the study involved an experimental class of 15 students and a control class of 18 students. A pretest-posttest control group design was applied: the experimental class used real industrial products in FEA and simulation learning, while the control class used textbooks or job sheets. Research stages included identifying product problems, redesigning, conducting FEA analysis and simulation, comparing old and new product results, and concluding recommendations. The study emphasizes student creativity in addressing product design challenges, highlighting how creative processes can produce measurable impacts on product evaluation. Findings reveal significant improvements in creativity when students learn through real industrial applications. This research contributes to strengthening university–industry partnerships, ensuring sustainable and impactful learning to enhance industrial product quality